NEW COMPLEX SELENITO AND OXALATO ADDUCTS CONTAINING SnPh3 AND SnPh2 RESIDUES: SYNTHESIS AND SPECTROSCOPIC STUDIES - SEYDI MANSOUR SECK; WALY DIALLO; LIBASSE DIOP; LORENZO STIEVANO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Three new organotin complexes (two selenito and an oxalate one) adducts have been synthesized and studied by infrared and Mössbauer techniques. A discrete structure is suggested with a bi-unidentate selenito oxyanion and trans bipyramidal SnPh3 residue; the oxalato adduct can be seen as an insertion compound between C2O4(SnPh3)2 and [Cu(En)3]C2O4•4SnPh2C2O4. This last compound has a discrete ionic structure with cis coordinated SnPh2 residues.